Legal aspect of credit cards in Malaysia: a review / Mohamad Hashim - Hashim, Mohamad (Faculty of Law, 1987)
The writer's objective in producing this project paper is to analyse the law relating to consumer credit transaction, since this area of law is new to us. In this work, among other things, this paper traces the history of credit card and its development together with the present law as it stand in Malaysia. It also discusses the mechanics of different types of credit cards. In connection with this, the meaning and nature of credit card transaction between the parties are also being emphasized. Contractual relationship between the parties under the Common Law and Malaysia are also included. In addition, the legal liabilities of the parties in their different contractual relationship is also discussed. Because these traditional contract laws do not give adequate protection to the cardholder (unauthorised use of credit card) in all cases, a chapter on this has been included. This project paper is concluded with some recommendations, as to how the problem can be solved so as to fit the position in Malaysia.